2016
DOI: 10.1007/s00586-016-4379-6
|View full text |Cite
|
Sign up to set email alerts
|

The ability of external immobilizers to restrict movement of the cervical spine: a systematic review

Abstract: Purpose To review the ability of various types of external immobilizers to restrict cervical spine movement. Methods With a systematical review of original scientific articles, data on range of motion, type of used external immobilization device and risk of bias were extracted. The described external immobilization devices were grouped and the mean restriction percentage and standard deviation were calculated. Finally, each device was classified based on its ability to restrict movement of the cervical spine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
17
0
3
Order By: Relevance
“…Any unfavourable handling might aggravate injuries, particularly to the neck, head, and spinal cord (which includes the cervical spine). For this reason, medical professionals were consulted during all design stages of ResQbot 2.0, and a survey of the literature was carried out [48][49][50][51][52][53][54][55][56][57].…”
Section: Medical Considerations and Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Any unfavourable handling might aggravate injuries, particularly to the neck, head, and spinal cord (which includes the cervical spine). For this reason, medical professionals were consulted during all design stages of ResQbot 2.0, and a survey of the literature was carried out [48][49][50][51][52][53][54][55][56][57].…”
Section: Medical Considerations and Researchmentioning
confidence: 99%
“…According to our literature review, it was found that spinal cord injuries and unstable fractures are some of the major concerns. Such injuries can occur either at the tetraplegic (the neck region) or paraplegic level (lower back region) [48][49][50][51][52][53][54][55][56][57]. Injuries at the tetraplegic level can cause impairment or loss of motor or sensory functions in the cervical segments of the spinal cord, affecting arms and legs [48].…”
Section: Medical Considerations and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Philadelphia-Orthese) zum Einsatz kommen. Eine ausführliche Übersicht über das Stabilisierungspotenzial der auf dem Markt befindlichen Zervikalorthesen bietet [16].…”
Section: Konservative Therapieunclassified
“…Should critical damage be present in the cervical spine, further motion could cause further injury or death. Research has shown that cranio-thoracic stabilization methods such as sandbags or stabilization blocks upon a stretcher can nearly completely stabilize the cervical spine, without the use of a cervical collar [7]. This thus forms the basis for the necessity and function of the proposed head stabilization device.…”
Section: Introductionmentioning
confidence: 99%